The Economy of Uzbekistan - Muratbaevich, Davletov Jasur (European Journal of Life Safety and Stability (2660-9630), 2022)
in this article we decided to consider the economy itself, as well as the economy of Uzbekistan. At the same time, we analyze the types of economy with what they consist of. With this, we will analyze the history of the emergence of the economy itself in Uzbekistan and in other countries.